Locas de felicidad, cronicas travestis y otros relatos, in the light of Pedro Lemebel - Rivera Pinilla, Diana (Cuadernos de Literatura, 2019)
Around the research with focus on gender and identity on the book Locas de felicidad. Crónicas travestis y otros relatos (2009) by Colombian writer John Better Armella, has proposed a direct intertextuality between this text and the literary project of the Chilean writer Pedro Lemebel. This intertextuality supports, as will be observed in the present article, the construction of a literary community that feeds a Latin American homoerotic tradition, by discovering an artistic, aesthetic and axiological symbiosis that is presented between the work of Better and works such as Loco afán: crónicas de sidario (1996) o Tengo miedo torero (2001).